Perubahan Biokimia dan Fisiologi Benih pada Berbagai Tingkat Kemasakan Buah Mengkudu - Rosdiana Ngitung, . (bionature, 2008)
This research was conducted to provide Morinda seeds that have certain quality as plant ingredients through use of seed with physiologies ripe.This research was conducted in Green House and Experimental Farm of Biologyâ€™s Departement FMIPA if State University of Makassar (UNM that goes on February till August 2008. This test was using Random Plan Group (RPG) of one factor was ripe degree of seed with three levels,that is : old Greed Fruits Colours, Yellow Fruit Colors,and white Fruits Colors. The treatment was repeats according to location of the fruits that had taken that ware up branch, middle part branch, and down part branch. Biochemistry test was on water degrees (%), carbohydrate degrees (%) (Quantifying of sugar degrees, essence and fiber degrees), protein degrees (%), fat degrees (%), and ash degrees (%). Viability and vigor test was on dry seed weight (g), water seed degrees (%), and dry sprout weight (g), sprout power (%), and sprout speed degrees was 95%. Result of the test that the ripe degrees of old Green Fruits Colors was called M-1 Stadium, Yellow Fruits Colors was called M-2 Stadium, and white Fruits Colors was called M-3 Stadium. According to biochemistry changing and physiology so that can be known that M-2 Stadium seeds had Morphologies Ripe (MR), and M-3 Stadium seeds had Physiologies Ripe (PR) Â  Keywords : morinda, seeds, ripe degrees